Applied computer sciences in engineering : 6th Workshop on Engineering Applications, WEA 2019, Santa Marta, Colombia, October 16-18, 2019, Proceedings /: 6th Workshop on Engineering Applications, WEA 2019, Santa Marta, Colombia, October 16-18, 2019, Proceedings. (2019) - Unknown
No abstract available